Cooperative learning in physical education lessons - literature review - Zach, Sima; Shoval, Ella; Shulruf, Boaz (Frontiers in Education, 2023)
Cooperative learning in physical education classes is perceived as beneficial. The aim of this article was to examine whether field studies that include cooperative learning in their physical education intervention programs provide applicable datato allow teachers to choose the optimal teaching strategy in line with their teaching goals. A systematic review of 44 research studies, published between 2000-2020, was conducted. Data related to teaching strategies and outcomes were compiled and discriminant function analysis was conducted, to classify the articles according to positive outcomes reported/not reported. Our results suggest a partial association between a range of cooperative teaching strategies (including Jigsaw, Learning Team, Complex, and Complex Instruction, as well as the cooperative learning model and combined strategies) and learning outcomes in four domains (social, physical, affective, and cognitive). Our literature review reveals that while the published data is valuable, additional research is needed to complete the picture.